TOPICAL ANTIBACTERIAL AGENTS UNDER CONDITIONS OF ANTIBIOTIC RESISTANCE OF THE MICROBIOME (AN ANALYTICAL REVIEW OF THE PROBLEM AND PROSPECTS FOR THE DEVELOPMENT OF NEW TOPICAL ANTIBACTERIAL (ANTISEPTIC) AGENTS) - V.H. Kravchenko; A.V. Kravchenko; Ya.O. Yemchenko; M.O. Dudchenko (Проблеми екології та медицини)
The problem of antibiotic resistance is currently one of the most urgent challenges for public health at the global level. An assessment by international experts shows that the resistance of microorganisms to antimicrobial agents is the cause of more than 700.000 deaths annually. Hence, only in the countries of the European Union, more than 25 thousand people die every year from infections caused by antibiotic-resistant bacteria. Despite the widespread use of systemic antibiotics in all fields of medicine, topical treatment of pathological processes continues to successfully serve in dermatology, gynecology, pediatrics, surgery, dentistry, and other areas of healthcare. Worldwide, one can observe a significantly increased interest in the development of topical antiseptic (non-antibiotic by origin) agents and their introduction into clinical practice, both for separate use and in combination with specific medications of systemic action (iodine derivatives, chlorhexidine bigluconate, cidipol, cimesol, etc.). We analyzed the current crisis situation in medicine and its causes related to the progressive polyresistance of the microbiome to antibiotics. The paper provides an overview of modern antibacterial, antibiotic and antiseptic agents on the domestic pharmaceutical market. We draw the attention of scientists and the creative medical community to the insufficient number of domestic innovative developments of antibacterial drugs and the importance of a demanding attitude to antibiotic treatment in connection with polyresistance of microbial flora. The study emphasizes that the development of new non-toxic medicinal products and a wider introduction of already known topical antibacterial, antiseptic, and anti-inflammatory agents with proven effectiveness and a scientifically based application scheme are extremely relevant and necessary under conditions of antibiotic resistance of the microbiome.